Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Je suis une maudite sauvagesse = Eukuan nin matshimanitu innu-iskueu - Antane Kapesh, An (Leméac, 1976)
An Antane Kapesh signe un réquisitoire accablant contre les Blancs : « Quand le Blanc a voulu exploiter et détruire notre territoire, il n'a demandé de permission à personne, il n'a pas demandé aux Indiens s'ils étaient d'accord. »
Donné en lecture au cours POL5480, Chapitre 6 « La police et les tribunaux », p. 109-144 dans la dernière édition.
Keywords: amériques; approches et analyses; autochtones; cours; discipline; fem1000; fem3100; femmes* innues; féminisme décolonial; littérature; manifeste; militance; pol4105; pol5480; premier cycle; premières nations; québec; racisme; racisme systémique; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

From the center: feminist essays on women's art - Lippard, Lucy R. (E.P. Dutton, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper & Row, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

Môman travaille pas, a trop d'ouvrage! - Théâtre des Cuisines; O'Leary, Véronique (Les éditions du remue-ménage, 1976)
« Môman travaille pas, a trop d'ouvrage! est le premier livre publié par les Éditions du remue-ménage en 1976. Pièce de théâtre marquante, drôle et vitriolique, qui appelait à une révolution tous azimuts, elle a été coécrite à l'époque par une troupe de théâtre de combat s'intéressant spécifiquement à l'exploitation des femmes, le Théâtre des cuisines. Le livre étant épuisé depuis plusieurs années, il était plus que temps de remettre en circulation ce joyau du féminisme et du théâtre québécois ; joyau qui, hélas, est plus que jamais d'actualité, lorsqu'on pense aux questions de travail domestique, de travail de soins, de charge mentale et d'invisibilisation. Les codirectrices de la collection LA NEF, Marie-Claude Garneau, Marie-Claude St-Laurent et Marie-Ève Milot ont souhaité bonifier cette nouvelle édition de photos d'archives, d'un avant-propos de Véronique O'Leary, porte-parole de la troupe, et d'une préface de Naïma Hamrouni, dont les travaux portant sur la philosophie féministe, le care et la justice sociale permettent de prolonger les enjeux soulevés dans la pièce, et de les ancrer dans les luttes actuelles. »– Résumé de l'éditeur.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; arts; canada; cours; discipline; féminisme matérialiste; lit3495; militance; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

La jeune née - Cixous, Hélène; Clément, Catherine (Union générale d'éditions, 1975)
La jeune née est un texte phare du mouvement féministe moderne. Hélène Cixous et Catherine Clément y mettent en avant le concept d'écriture féminine, explorant la façon dont la sexualité et l'inconscient des femmes façonnent leur imaginaire, leur langage et leur écriture.
Keywords: 1900-1999; 1970-1979; cours; discipline; europe; fem1000; france; incontournable; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; écriture des femmes*; études culturelles; études littéraires

A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Le corps lesbien - Wittig, Monique (Éditions de minuit, 1973)
Le lesbianisme est traité selon une dimension poétique : le corps féminin est énuméré selon ses différentes parties, et se présente comme un manifeste de la révolte féminine, écrit par une femme, pour les femmes.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; corps; corps féminin; cours; discipline; europe; fem1000; france; lesbianisme; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires

Vous les entendez? - Sarraute, Nathalie (Gallimard, 1972)
Un soir après le dîner, un père de famille reçoit la visite d'un voisin et ami. Tandis que les deux hommes s'installent au salon autour d'une table basse où est déposée une statuette, les enfants s'éclipsent poliment dans leur chambre. Autour de l'oeuvre d'art naît une conversation où se mêlent curiosité, admiration et désirs... Mais leur contemplation est dérangée par les rires en cascade qui leur parviennent depuis l'étage. Rires innocents ou sarcasmes ? Futilités ou rébellion ?
Section: 222 pages
Keywords: arts; cours; discipline; lit2815; premier cycle; roman; thématiques; écriture des femmes*; écriture expérimentale; études littéraires